2022
DOI: 10.1186/s12882-022-03025-w
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for the prediction of acute kidney injury during the perioperative period: systematic review and Meta-analysis of diagnostic test accuracy

Abstract: Background Acute kidney injury (AKI) is independently associated with morbidity and mortality in a wide range of surgical settings. Nowadays, with the increasing use of electronic health records (EHR), advances in patient information retrieval, and cost reduction in clinical informatics, artificial intelligence is increasingly being used to improve early recognition and management for perioperative AKI. However, there is no quantitative synthesis of the performance of these methods. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…Some may be persuaded that other tools may help identify AKI early, including artificial intelligence (AI). The role of AI will undoubtedly influence the practice of medicine significantly in the future and recent meta-analyses of currently published models showed promising performance for early prediction of postoperative AKI [15]. However, a word of caution.…”
Section: Discussionmentioning
confidence: 99%
“…Some may be persuaded that other tools may help identify AKI early, including artificial intelligence (AI). The role of AI will undoubtedly influence the practice of medicine significantly in the future and recent meta-analyses of currently published models showed promising performance for early prediction of postoperative AKI [15]. However, a word of caution.…”
Section: Discussionmentioning
confidence: 99%
“…[21] However, a simple decision tree model may have a low classification performance for other ML models, and it is difficult to process noisy datasets. [10,[21][22][23] To address these challenges, we used a dataset with no missing data, and feature selection was aided by the least absolute shrinkage, and selection operator regression method. [13] In the unbalanced data, the specificity or local accuracy of the majority class exceeded that of the minority class.…”
Section: Discussionmentioning
confidence: 99%
“…[16] This study provides additional evidence to the finding of previous studies that ML models outperform logistic regression in predicting AKI. [10,11,26] Although the XG Boost algorithm is known to exhibit better performance than other algorithms, it requires more time for model training. [25,27] Our study demonstrated a good classification performance with only hyperparameter tuning through Grid Search CV, without using XG Boost or gradient boosting tree algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations